Views of contraceptive service delivery to young people in the UK: a systematic review and thematic synthesis. Issue 2 (31st March 2011) - Baxter, Susan; Blank, Lindsay; Guillaume, Louise; Squires, Hazel; Payne, Nick
Abstract : Background and methodology: Despite widespread availability of contraceptives and increasing service provision in the UK, rates of teenage pregnancy remain a concern. It has been suggested that young people face particular obstacles in accessing services, leading to a need for specialist provision. This systematic review examined the literature reporting views of service providers and young people. Data were synthesised in order to develop key themes to inform the development of contraceptive services for this population. Results: A total of 59 papers reporting studies carried out within the UK were included. Forty-five of these provided qualitative or mixed method data and 14 reported survey findings. Seven key themes were identified: perceptions of services; accessibility; embarrassment; anonymity and confidentiality; the clinic environment; the consultation; and service organisation. Conclusions: This review suggests that the most significant concern for young people is the preservation of anonymity and confidentiality. There seems to be a need for young people to be given greater assurances about this, with process and environmental changes suggested. The fear of staff being critical or unfriendly also presents a considerable obstacle to some young people. Issues of service accessibility – such as convenience of location and opening hours – are also highlighted, with lifestyle factors and restrictions on where under-18s can go suggested as important aspects. The review suggests that varying preferences among young people with regard to which service to access requires choice to be preserved and, where possible, extended. This requires services to work effectively together to consider provision across a locality.